Investigation on the Influence and Interaction Effect of Phytosterols on the Polycyclic Aromatic Hydrocarbons Delivery in Tobacco Based on Uniform Design - Du, You; Xue, Fang; Liu, Hailong; Shi, Fengcheng; Dai, Ya; Li, Dongliang; Chen, Hua (Asian Journal of Chemistry, 2013)
In this study, the impact of four free phytosterols (cholesterol, stigmasterol, b-sitosterol and campesterol) on the delivery of 15 polycyclic aromatic hydrocarbons in tobacco was analyzed by GC/MS, the experiments were designed and carried out basing on uniform design and the results were analyzed by a second-order polynomial stepwise regression model. With regression analysis, the results highlight that those four free phytosterols as well as their interaction effect significantly influenced the delivery of polycyclic aromatic hydrocarbons and there may existed an obvious linear relationship. The analysis results of benzo[a]pyrene indicated that cholesterol, stigmasterol and campesterol have a positive influence on the delivery of benzo[a]pyrene while the interaction effect between cholesterol and campesterol, between stigmasterol and campesterol, between b-sitosterol and campesterol have a negative influence on the delivery of benzo[a]pyrene.